Adherence to vitamin supplementation following adolescent bariatric surgerya2. (16th April 2013) - Modi, Avani C.; Zeller, Meg H.; Xanthakos, Stavra A.; Jenkins, Todd M.; Inge, Thomas H.
Abstract Objective: Adolescents with extreme obesity, who have undergone bariatric surgery, must adhere to many lifestyle and nutritional recommendations, including multivitamin therapy. Little is known about multivitamin adherence following adolescent bariatric surgery. Design and Methods: The present study aims to document self‐reported and electronically‐monitored adherence to multivitamins, determine convergence between self‐report and electronic monitoring adherence for multivitamins, and identify barriers to multivitamin adherence for adolescents who have undergone bariatric surgery. Results: The study used a prospective, longitudinal observational design to assess subjective (self‐reported) and objective (electronic monitors) multivitamin adherence in a cohort of 41 adolescents (Mean age = 17.1 ± 1.5; range = 13‐19) who have undergone bariatric surgery at Cincinnati Children's Hospital Medical Center. Mean adherence as derived from electronic monitoring for the entire 6‐month study period was 29.8% ± 23.9. Self‐reported adherence was significantly higher than electronically monitored adherence across both the 1 and 6‐month assessment points (z = 4.5, P < 0.000 and z = 4.0, P < 0.0001, respectively). Forgetting and difficulty swallowing multivitamins were the two primary barriers identified. While there are no established data regarding best practice for multivitamins following bariatric surgery, high rates of nonadherence to multivitamin therapy were observed in adolescents who had undergone bariatric surgery with forgetting and difficulty swallowing pills as reported barriers to adherence. Conclusion: These high rates of nonadherence to multivitamin therapy should be considered when devising treatment and family education pathways for adolescents considering weight loss surgery.